2008
DOI: 10.1111/j.1475-5890.2008.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

The Anticipated Capitalisation Effect of a New Metro Line on Housing Prices*

Abstract: Housing units with closer access to public transportation enjoy a higher market value than those with similar characteristics but poorer access. This difference can be explained by the lower cost of transport to the main workplaces and shopping areas in town. For this reason, investments in public transport infrastructure, such as building a new metro line, are capitalised totally or partially into land and housing prices. This work empirically analyses the degree of capitalisation into housing prices of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 35 publications
1
66
0
6
Order By: Relevance
“…Similar work on the economic impact of public transit systems began in the 1970s and 1980s (Cervero, ; Cervero, ; Knight & Trygg, ) and generally supports the idea that station proximity increases property values and thus development intensity, primarily when the service itself is frequent and reliable, when the system is planned in conjunction with supportive land use policies, and is built in areas with high existing economic growth and development potential (Agostini & Palmucci, ; Cervero, ; Cervero, ; Cervero, ; Damm, Lerman, Lerner‐Lam, & Young, ; Golub, Guhathakurta, & Sollapuram, ; Hess & Almeida, ; Knaap, Ding, & Hopkins, ; Knight & Trygg, ; Landis, Guhathakurta, & Zhang, ; Seo et al, ; Weinberger, ; Weinstein & Clower, ). While other researchers have pointed out that the economic benefits observed due to transit systems may be (1) simply a refocusing of development that would have occurred somewhere else (e.g., the suburbs) or (2) predominantly due to regional economic conditions (Giuliano, ; Schuetz, ; Vessali, ), a recent meta‐analysis has confirmed that, overall, transit generally confers property value benefits to adjacent areas (Mohammad, Graham, Melo, & Anderson, ).…”
Section: Economic Effects Of Transportation Systemsmentioning
confidence: 63%
“…Similar work on the economic impact of public transit systems began in the 1970s and 1980s (Cervero, ; Cervero, ; Knight & Trygg, ) and generally supports the idea that station proximity increases property values and thus development intensity, primarily when the service itself is frequent and reliable, when the system is planned in conjunction with supportive land use policies, and is built in areas with high existing economic growth and development potential (Agostini & Palmucci, ; Cervero, ; Cervero, ; Cervero, ; Damm, Lerman, Lerner‐Lam, & Young, ; Golub, Guhathakurta, & Sollapuram, ; Hess & Almeida, ; Knaap, Ding, & Hopkins, ; Knight & Trygg, ; Landis, Guhathakurta, & Zhang, ; Seo et al, ; Weinberger, ; Weinstein & Clower, ). While other researchers have pointed out that the economic benefits observed due to transit systems may be (1) simply a refocusing of development that would have occurred somewhere else (e.g., the suburbs) or (2) predominantly due to regional economic conditions (Giuliano, ; Schuetz, ; Vessali, ), a recent meta‐analysis has confirmed that, overall, transit generally confers property value benefits to adjacent areas (Mohammad, Graham, Melo, & Anderson, ).…”
Section: Economic Effects Of Transportation Systemsmentioning
confidence: 63%
“…However, the relationship between transit access and housing prices is not necessarily straightforward. For example, the premium on house prices may be variable over time, even appearing before the transit line is constructed, in anticipation of future benefits (Agostini and Palmucci ; Knaap et al ; McMillen and McDonald ). House values are higher near transit stations in Atlanta, but not too near, as negative externalities such as increased traffic, noise, and potential for crime are dominant immediately adjacent to stations (Bowes and Ihlanfeldt ), a situation similar to that observed in Helsinki (Laakso ).…”
Section: Transit and Housing: The Neoclassical Perspectivementioning
confidence: 99%
“…That study concludes that public transit has its largest impact on local home prices and gentrification when the new transit connects an area to a vibrant downtown. Based on data from Santiago et al (2008) find that the news of announced new subway stations is capitalized into local property prices. Other research has investigated the effects of new green space.…”
mentioning
confidence: 99%